Normization of Dynamic-Impatience Test in the Field of thought Excitement - Alikhani, Mohammad Sadegh; Kazemi Haghighi, Naseruddin (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The aim of this research is the norming of the Test of Dynamism-Impatience in the realm of emotion of thought. Methodology: The population of this study consists of students aged 15 to 17 years in Tehran. The sample includes 973 students, selected randomly through multistage cluster sampling from the 22 districts of Tehran. The instrument used in this research is the Test of Dynamism-Impatience in the realm of emotion of thought, which contains 69 questions. This test was initially administered to three hundred individuals, and after analysis and examination, the final test with the same 69 questions was conducted and analyzed. The test overall comprises three subscales: cognitive resilience, emotional tenacity, and impatience. The reliability of the test was examined through retesting, and the results showed that the correlation between the components of all three examined realms of the test was above 0.9 and significant at the 0.01 level (P>0.01), indicating high reliability of the test. Findings: The validity of the test was analyzed and evaluated through construct validity using factor analysis. The initial (exploratory) factor analysis was conducted to extract the main factors of the three fundamental realms of the test. It was hypothesized that the test overall consists of twelve basic components, and exploratory factor analysis revealed that the test in total is made up of eight main components. These components were analyzed through confirmatory factor analysis. Conclusion: The results showed that the standardized factor loadings of all items are higher than 0.32, indicating that all items of this test have the necessary potential for measuring the latent variables extracted and are supported by confirmatory factor analysis. Finally, the normative tables of the test are also presented.